A case of subcutaneous panniculitis-like T-cell lymphoma of the cheek. Issue 5 (September 2017) - Sakata, Ken-ichiro; Yamazaki, Yutaka; Kuroshima, Takeshi; Ohga, Noritaka; Satoh, Chiharu; Sakakibara, Noriyuki; Kitagawa, Yoshimasa
Abstract: Subcutaneous panniculitis-like T-cell lymphoma (SPTL) was first reported as T-cell lymphoma resembling panniculitis. Many of the lesions are observed in the upper and lower extremities and trunk, whereas occurrence in the facial area is extremely rare. Our patient was a 19-year-old male who reported of some swelling in the left facial area 5 months prior to the initial examination. Originally misdiagnosed as a scar caused by accidental biting the buccal mucosa when first presenting at the Department of Dermatology of a local hospital, the patient was eventually referred to our department upon request for resection. Upon initial examination, a high degree of diffuse swelling extending from the left cheek to the eye socket was observed. Intraoral observation showed no pathological findings or tooth infections. MRI showed an unclear boundary in the subcutaneous fat layer of the left buccal region. Clinical and image findings with a cheek biopsy confirmed a diagnosis of Weber–Christian disease. The pathological diagnosis was SPTL. Chemotherapy resulted in disappearance of the swelling. The patient has remained relapse-free for 5 years.